Antimicrobial activity of a bacterial nanocellulose film functionalized with nisin Z for prospective burn wounds treatment - Melro, Liliana (2022)
Supplementary Materials: The following are available online at https://www.mdpi.com/article/10 .3390/eca2022-12708/s1